Reproductive traits and age of barbeled plunderfishes from the Weddell Sea. Issue 4 (August 2020) - La Mesa, Mario; Donato, Fortunata; Riginella, Emilio; Papetti, Chiara; Parker, Elyse; Near, Thomas J.
Abstract: The genus Pogonophryne is the most species-rich genus of barbeled plunderfishes (Artedidraconidae) and includes more than 25 poorly known species endemic to the Southern Ocean. In this study, we provide new data on the age and reproductive traits of some species of Pogonophryne from the southern Weddell Sea, inferred through otolith reading and histological analyses of gonads. Individual age estimates ranged between 16 and 18 years for Pogonophryne barsukovi and Pogonophryne immaculata and between 10 and 22 years for Pogonophryne scotti . As is commonly found in notothenioids, P. barsukovi followed a group-synchronous type of ovarian development, with pre-vitellogenic and vitellogenic oocytes forming two well-separated egg-size groups. A single spawning female in the sample produced ~1097 eggs and 7.9 eggs g -1 . The sample of P. immaculata consisted exclusively of developing males, with testes composed of cysts of spermatogonia, spermatocytes and spermatids. Pogonophryne scotti was the most abundant species, including relatively small males at immature or developing stages of gonad development. Larger females were regressing, being characterized by ovaries with postovulatory follicles and atretic oocytes. Based on the macroscopic and histological analyses of gonads, the spawning season would take place in autumn for P. barsukovi and P. immaculata and in spring–early summer for P. scotti .